Web-based examinations in higher education (WEBiHE) institutions in the Sub-Saharan Africa region: a systematic review of 2013–2024 literature - Brandford Bervell; Dickson Okoree Mireku; Prosper Dzifa Dzamesi; Akua Tiwaa Buabeng-Boateng; Bernard Yaw Sekyi Acquah (Cogent Education)
The purpose of this study was to map the distribution of publications on web-based examination in higher education institutions (HEIs) in Sub-Saharan Africa (SSA) through a systematic literature review. The review included 159 web-based examination-related studies from 2013 to 2024. Findings revealed that most studies related to web-based examinations were published in 2022 and 2023. Most institutions 59 (37.16%) using web-based examination were from Western SSA, followed by Eastern SSA with 15 institutions (9.45%) signifying a potential heightened interest in scholarly works around the phenomenon in these regions. Multiple choice questions (MCQs) were the most frequently specified type of web-based test. The most significant concern for students about web-based examination was access to a stable internet connection, whereas that of lecturers’ was the potential for cheating, especially in situations where supervision was limited. Additionally, assessment efficiency and effectiveness were the key motivations for the adoption of web-based examination by higher education institutions in SSA. Finally, the most frequently discussed solution to enhance web-based examination was investment in infrastructure and technology upgrades. Based on the findings from the literature review, recommendations were provided to offer a roadmap for future research and practice in conducting web-based examination within SSA higher education delivery.